First quantification of <2 μm clay, <0.2 μm ultrafines and solids wettability in process streams from naphthenic froth treatment plant at commercial mined oil sands operations. (1st February 2019) - Mercier, Patrick H.J.; Tyo, Daniel D.; Zborowski, Andre; Kung, Judy; Patarachao, Bussaraporn; Kingston, David M.; Couillard, Martin; Robertson, Gilles; McCracken, Thom; Ng, Samson
Abstract: For the first time in oil sands industry, the absolute amounts of <2 μm clay and <0.2 μm ultrafine solids were quantified in commercial streams from the naphthenic froth treatment (NFT) process used by mined oil sands operators. The sample suite studied comprised seven representative NFT streams collected at a commercial plant including: one bitumen froth feed (F1), two naphtha-diluted bitumen products (P1, P2) and four tailings (T1, T2, T3, T4). The solids present in each of the seven NFT streams were fractionated quantitatively based on particle size and solids wettability using three original quantitative separation techniques presented here. First, clay-ultrafines (CUF) separation technique allows to fractionate solids into four distinct particle-size fractions: coarser solids (CS), >2 μm; total clays (TC), <2 μm; coarse clays (CC), 0.2–2 μm; and ultrafines (UF), <0.2 μm. Second, toluene/water (T/W) interfacial wettability (WET) fraction separation technique enables separation of solids into four distinct fractions: Hydrophilic Solids (HPS) partitioning into the aqueous phase (carbon <5% w/w); Intermediate Solids (IS) only weakly held at the T/W interface (carbon 6–10% w/w); organic-rich solids (ORS) remaining strongly held at the T/W interface (carbon 15–20% w/w); high speed centrifugation solids (HSCS) remaining dispersed in the bitumen-toluene phase (carbon >20% w/w). And third, toluene/water interfacial total solids (TS) separation permits to isolate all-at-once the entire solids fraction comprised in a given sample. The analytical procedures developed to apply these three techniques are outlined in detail, and compared to two standard methods used in the oil sands industry: Soxhlet-Dean and Stark extraction method and COSIA Unified Fines Method for minus 44 µm material and for Particle Size Distribution (PSD). From quantitative results obtained by CUF, WET and TS techniques and industry standard PSD methods, the following key results arise. Most notably, CUF technique developed here showed >10 wt% ultrafines in samples T4, P1 and P2, whereas industry standard PSD methods (laser diffraction PSD data) did not notice any significant differences between the seven samples. The UF contents per total solids increase in going from froth F1 (∼2.5 wt%) through product P1 (∼9.3 wt%) to product P2 (∼11 wt%). Tailings T4 has the highest proportion of UF (∼12 wt%) amongst the four tailings, and also has the highest amounts of HPS, TC, and CC of any streams. NFT stream T4 therefore likely results from a separation process which selectively removes the smaller hydrophilic solids. The ORS and HSCS proportions per total solids increase in going from froth F1 through product P1 to product P2. For product P2, the ORS and HSCS contents account respectively for ∼70 wt% and ∼10 wt% of the solids contained in this sample. By contrast, as ORS and HSCS increase, the HPS contents decrease correspondingly. This inverse behavior between HPS and ORS + HSCS contents demonstrates the preferential removal of hydrophilic solids by the NFT processes. X-ray diffraction patterns measured for HSCS fractions separated from froth F1 and products P1 and P2 are virtually the same. This suggests that HSCS solids are present in the inlet froth and go through the entire NFT circuit without being affected by any of the different separation unit operations integrated in the NFT process flowsheet.